2015
DOI: 10.5090/kjtcs.2015.48.6.398
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Clinical Outcomes after Modified High Ligation and Segmental Stripping of Incompetent Small Saphenous Veins

Abstract: BackgroundThe aim of this study was to evaluate the midterm clinical outcomes after modified high ligation and segmental stripping of small saphenous vein (SSV) varicosities.MethodsBetween January 2010 and March 2013, 62 patients (69 legs) with isolated primary small saphenous varicose veins were enrolled in this study. The outcomes measured were reflux in the remaining distal SSV, the recurrence of varicose veins, the improvement of preoperative symptoms, and the rate of postoperative complications.ResultsNo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…7 In a recent study, however, the recurrence rate was shown to be 4.3% among patients undergoing modified high ligation and segmental stripping, although the sample size was small. 10 In our study, on the other hand, the recurrence rate was 31.1% among patients undergoing high ligation + segmental stripping. This can be attributed to the small sample size and to the fact that endovascular treatment methods were not popular at the beginning of the endovascular era when most patients underwent conventional surgery.…”
Section: Discussionmentioning
confidence: 42%
“…7 In a recent study, however, the recurrence rate was shown to be 4.3% among patients undergoing modified high ligation and segmental stripping, although the sample size was small. 10 In our study, on the other hand, the recurrence rate was 31.1% among patients undergoing high ligation + segmental stripping. This can be attributed to the small sample size and to the fact that endovascular treatment methods were not popular at the beginning of the endovascular era when most patients underwent conventional surgery.…”
Section: Discussionmentioning
confidence: 42%
“…Actualmente, la tarifa en la medicina privada de una ablación oscila entre los USD$ 2.500 y los USD$ 4.000, que se reducen a USD$ 1.500-2.000 en el caso de una safenectomía. Como consecuencia, la mayoría de los servicios públicos de salud a nivel mundial excluyen la ablación de su lista de coberturas asistenciales gratuitas 1,28 . En el caso de una safenectomía quirúrgica unilateral ambulatoria concertada con el Sistema Público Aragonés de Salud, nuestra Clíni-ca factura USD$ 950, incluidos los honorarios del cirujano y del anestesista, consulta, estudio preoperatorio, material fungible y gastos de hospitalización; esto, en vista de las buenas prestaciones que se han obtenido y su bajo costo, le permiten mantener su vigencia.…”
Section: Discussionunclassified